Quality changes, potential spoilage organisms, and shelf-life prediction of brackish river prawn (Macrobrachium macrobrachion) at different storage temperatures - Dabadé, D. Sylvain; YESSOUFOU, Nadiath; ADIDO, Lionel; AZOKPOTA, PAULIN (My University, 2023)
The brackish river prawn (Macrobrachium macrobrachion) is a species of commercial importance in West Africa. However, like other fishery products, it is prone to deterioration due mainly to microbial activities. The present study aimed at evaluating the spoilage characteristics of M. macrobrachion and predicting the growth of the main spoilage bacteria as well as the shelf-life of the product as a function of storage temperature. Freshly caught brackish river prawn samples from Lake Aheme were aerobically stored at 0, 7, 15, and 28 ◦C and, at pre- determined times during storage, they were taken for microbiological, chemical, and sensory analysis. At sensory rejection times, the spoilage potential of 185 isolates from specific groups of organisms enumerated was assessed in prawn of which the endogenous microbiota was heat inactivated. Isolates capable of producing strong off-odor were identified using 16S rRNA sequencing. Models predicting the maximum growth rate of Pseudomonas spp. and H2S-producing bacteria in the brackish river prawn as well as the shelf-life of the product were developed. These models were validated using an independent experiment during which prawn was stored at 0, 4, 10, and 25 ◦C. Results showed that Pseudomonas spp. at 0 ◦C, Pseudomonas spp. and H2S-producing bacteria at 7 ◦C, and H2S-producing bacteria at 15 ◦C and 28 ◦C were the dominant groups of microorganisms during storage. As expected, total volatile basic nitrogen, trimethylamine, and pH with initial values of 21.2 ± 3.0 mg- N/100 g, 4.1 ± 0.8 mg-N/100 g, and 7.46 ± 0.15 increased during storage reaching approximately 35 mg-N/ 100 g, 10 mg/ 100 g and 8, respectively at sensory rejection times which were 7 h at 28 ◦C, 1.2 d at 15 ◦C, 4.6 d at 7 ◦C, and 11.7 d at 0 ◦C. The main spoilage organisms were Citrobacter braakii at 28 ◦C, Citrobacter braakii, Pseudomonas kurunegalensis, and Shewanella bicestrii at 15 ◦C, Shewanella putrefaciens, Shewanella baltica, and Pseudomonas bubulae at 7 ◦C, and Pseudomonas versuta at 0 ◦C. The validation of the developed models showed an adequate agreement between the predicted and observed values. This study highlights the specific spoilage characteristics of the brackish river prawn and reveals that Gram-negative rod bacteria are the main spoilage organisms even at high storage temperatures, contrary to many earlier reports on the spoilage of tropical fishery products.
Keywords: Seafood spoilage; Pseudomonas versuta; Citrobacter braakii; Shewanella putrefaciens; TVBN